Novel antibody drug conjugates containing exatecan derivative-based cytotoxic payloads. Issue 6 (15th March 2016) - Nakada, Takashi; Masuda, Takeshi; Naito, Hiroyuki; Yoshida, Masao; Ashida, Shinji; Morita, Koji; Miyazaki, Hideki; Kasuya, Yuji; Ogitani, Yusuke; Yamaguchi, Junko; Abe, Yuki; Honda, Takeshi
Graphical abstract: Abstract: Trastuzumab conjugates consisting of exatecan derivatives were prepared and their biological activities and physicochemical properties were evaluated. The ADCs showed strong efficacy and a low aggregation rate. The exatecan derivatives were covalently connected via a peptidyl spacer (Gly-Gly-Phe-Gly), which is assumed to be stable in circulation, and were cleaved by lysosomal enzymes following ADC internalization into tumor tissue. These anti-HER2 ADCs exhibited a high potency, specifically against HER2-positive cancer cell lines in vitro. The ADCs, bearing exatecan derivatives which have more than two methylene chains, exhibited superior cytotoxicity. It was speculated that steric hindrance of the cleavable amide moiety could be involved in the drug release. The adequate alkyl lengths of exatecan derivatives (13, 14, 15 ) were from two to four in terms of aggregation rate. The ADC having a hydrophilic moiety showed good efficacy in a HER2-positive and Trastuzumab-resistant breast carcinoma cell model in mice.